Hygrometric Performances of Different High-Flow Nasal Cannula Devices: Bench Evaluation and Clinical Tolerance. - Delorme, Mathieu; Bouchard, Pierre-Alexandre; Simard, Serge; Lellouche, François (Respiratory Care, 2021)
BACKGROUND: High-flow nasal cannula (HFNC) is increasingly used for the management of respiratory failure. Settings include FIO2, total gas flow, and temperature target. Resulting absolute humidity (AH) at the nasal cannula may affect clinical tolerance, and optimal settings with respect to hygrometry remain poorly documented. METHODS: A bench study was designed to assess AH delivered by 4 HFNC devices (Optiflow, Airvo 2, Precision Flow, and Hydrate) according to flow, ambient temperature, and other available settings. Clinical tolerance of different levels of hygrometry (20, 30, and 40 mg H2O/L) was evaluated in 15 healthy volunteers. RESULTS: With FIO2 set at 1.0, normal ambient temperature, and settings made accordingly to the manufacturers' recommendations, mean ± SD AH was 42.2 ± 3.1, 39.5 ± 1.8, 35.7 ± 2.0, and 32.9 ± 2.7 mg H2O/L for the Airvo 2, Optiflow, Hydrate, and Precision Flow, respectively, (P < .001). AH dropped from -3.5 to -10.7 mg H2O/L (P <. 001) with high ambient temperature, except for the Precision Flow. Increasing flow did not significantly affect AH except for the Precision Flow (from 36.4 ± 1.6 to 29.8 ± 0.2 mg H2O/L at 10 and 40 L/min, respectively, [P < .001]). The lowest AH was encountered with the Optiflow set with noninvasive ventilation (NIV) mode, without compensation algorithm, and at high ambient temperature (14.2 ± 1.5 mg H2O/L). In studied subjects, AH significantly affected breathing comfort, reduced from 7.0 ± 1.0 to 3.0 ± 2.0 at 40 and 20 mg H2O/L, respectively, (P < .001). Comfort was similar at 30 and 40 mg H2O/L. CONCLUSIONS: When used according to manufacturer's recommendations and at normal ambient temperature, all the HFNC devices evaluated achieved satisfactory hygrometric output with respect to breathing comfort evaluated in healthy subjects (≥ 30 mg H2O/L). Substantial differences exist between devices, and optimal knowledge of their working principles is required as inappropriate usage may dramatically alter efficacy and clinical tolerance.